Persepsi Petani terhadap Lahan Pertanian Jagung dalam Perspektif Ekologi dan Ekonomi di Provinsi Jawa Tengah - Zuhri, Nur Muttaqien; Khamdi, Ali (Fakultas Pertanian, Universitas Timor, 2024)
Ecological and socio-economic roles can contribute to the productivity of corn commodities. The decreased productivity of corn can be influenced by farmers' perceptions of land use. The aim of the study was to analyze corn farmers' perceptions of different cultivation land uses in terms of ecological and economic benefits. The research was conducted in Central Java Province, which is a main center of corn production. Simple random sampling data from 210 corn farmer respondents were used in this study. Data analysis used in this study was non-parametric analysis of Mann-Whitney test. The results showed that corn farmers' perceptions can influence decisions in adopting land types. Then there are differences in perceptions between corn farmers in adopting land types (paddy field, paddy forest, community forest and community plantation forest) towards ecological and economic benefits. Meanwhile, there is a gap in knowledge about ecological and economic benefits among corn farmers in paddy fields, paddy forest and community forest. The policy makers need to be involved in designing and implementing policies related to sustainable land use for farmers, therefore increasing corn productivity.